Development of triple bottom line indicators for sustainability assessment framework of Malaysian palm oil industry - Lim, Chye Ing; Biswas, Wahidul (2018)
The production of crude palm oil has environmental, economic and social implications. A sustainability assessment framework is needed to improve the sustainability performance of crude palm oil production in a carbon-constrained economy. The objective of this paper is to develop Performance Measures for triple bottom line assessment in the Malaysian palm oil industry, which includes Key Performance Indicators and Higher Performance Indicators for implementing the sustainability assessment framework. The Performance Measures of the triple bottom line assessment were built on the framework of Lim and Biswas (Sustainability 7(12):16561–16587, 2015). The measures were further developed through a participatory approach involving stakeholders and area experts, including Government, Industry, Academia and Local Smallholders/Non-Government Organisations. The developed framework presents a final list of Performance Measures, Key Performance Indicators and Higher Performance Indicators using a structured process and introduces weighting factors to the indicators to reflect the difference in the perceived level of importance. The calculation methods of the assessment framework were verified, and finally, the framework was tested using hypothetical data.